Hubungan Pengetahuan Pemeliharaan Gigi Tiruan Lengkap Terhadap Kebersihan Gigi Tiruan Pasca Insersi (Relation Between Knowledge Of Full Denture Maintenance Toward Denture Hygiene Post Insertion) - Dyah Kurnia Aulia; Hestieyonini Hadnyanawati; Dewi Kristiana (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Background: Insertion of removable partial dentures and full dentures will cause ecological changes in the oral cavity and facilitate accumulation of plaque on the denture. The accumulation of plaque on the denture base is affected by duration of using dentures, type denture base material and knowledge of denture hygiene maintenance that was obtained from dentist's instruction. Objective: The objective of this research is to determine the relation between knowledge of full denture maintenance toward denture hygiene post insertion. Method: The type of research is analytic observational study with cross sectional approach. Knowledge of full denture maintenance was measured using a questionnaire while, dentures hygiene was measured using Ausberger and Elahi methods. The collected data were tabulated and analyzed with Spearman Rank Correlation test. Result and Conclusion: The result is the value of p = 0.00 <α = 0.005, yielding a correlation coefficient between knowledge of full denture maintenance toward denture hygiene of -0.907. This coefficient value indicates that the direction of the negative correlation. Negative correlation means that the relations are inversely proportional, the higher level of knowledge about removable denture maintenance, then the lower hygiene scores of full dentures. Keywords: full denture, denture hygiene, knowledge, denture plaque.